The message of Acts in Codex Bezae : a comparison with the Alexandrian tradition.: a comparison with the Alexandrian tradition. Acts 6.1-12.25 : from Judea and Samaria to the church in Antioch / Vol. 2, (©2006) - Unknown
No abstract available